PENGARUH PRODUK WISATA, DAN WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG DENGAN CITRA DESTINASI SEBAGAI VARIABEL INTERVENING (Studi Pada Obyek Wisata Colo Kudus) - Zakia, Sheila Zara; Widiartanto, Widiartanto (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
Tourism is one of the fastest growing industries today. Consequently, people think that travelling is alifestyle nowadays. The developing tourism business industry creates high competition among tourismdestinations. The organizers of tourism destinations are competing to increase the number of tourist visitors.Tourism Site in Colo Kudus which is the main tourist destination of Kudus Regency, is prioritized to gain morevisitors. However since 2010 until 2014 there was a fluctuation in decline of tourist visitors.The purpose of this study is to find out the influence of tourism products, and word of mouth to thedecision to visit the destination’s image as an intervening variable study of Tourism Site in Colo Kudus. Thetype of researh is explanatory research. Questionnaire were adopted for data collection in this study. Hundredpeople were employed as respondent by convenience sampling technique. The respondents were Tourism Site inColo Kudus who have made a purchase of at least two times over the last three years. This research is usesqualitative and quantitative analysis technique. Quantitative analysis use validity test, reliability test,correlation coefficient, two-stage regression analysis, the coefficient of determination, a signification test (ttest).The result of this research approved that tourism products (X1), and word of mouth (X2) simultaneouslycan influenced destination’s image (Y1) and decision to visit (Y2). According the result of two-stage regressionanalysis showed that visitors’ destination’s image (Y1) variable is not intervening variable word of mouth (X2)to the decision to visit (Y2) in this research.Based on the results, the researcher suggests that Tourism Site in Colo Kudus management has toimprove infrastructures such as roads and road signage, provision of public transportation, provide innovationon tourism products, so the tourist numbers can increase.